Harnessing liquid crystal attributes of near-unit photoluminescent benzothioxanthene photosensitizers - Duarte, Frederico (2024)
French National Research Agency ‘ANR’ for the project BTXI-Apogee ref: ANR-20-CE05-0029). D.P.S and K.M. acknowledge the MITI of the CNRS and the ANR (BTXI-Apogee, ANR-20-CE05-0029) for their PhD grants respectively. C. S. B. Gomes acknowledges the XTAL \u2013 Macromolecular Crystallography group (UCIBIO and i4HB) for granting access to the X-ray diffractometer. X-Ray infrastructure financed by FCT-MCTES through project RECI/BBBBEP/0124/2012. Publisher Copyright: © 2024 The Author(s)